Adipose-derived stem cells (ADSC) in the viability of random skin flap in rats - Suartz,Caio Vinicius (2014)
PURPOSE: To evaluate the effects of the adipose-derived stem cells (ADSC) in the viability of random skin flap in rats.METHODS: Thirty five adult male Wistar rats (weight 250-300 g) were used. ADSC were isolated from adult male rats (n=5). ADSC were separated, cultured and then analyzed. A dorsal skin flap measuring 10x4 cm was raised and a plastic barrier was placed between the flap and its bed. After the surgical procedure, the animals were randomized into two groups (n=15 each group), group control and group ADSC. In all groups the procedures were performed immediately after the surgery. The percentage of flap necrosis was measured on the seventh postoperative day.RESULTS: The ADSC were able to replicate in our culture conditions. We also induced their adipogenic, osteogenic and chondrogenic differentiation, verifying their mesenchymal stem cells potentiality in vitro.The results were statistically significant showing that the ADSC decreased the area of necrosis (p<0.05).CONCLUSION:The cells demonstrated adipogenic, osteogenic and chondrogenic differentiation potential in vitro.The administration of adipose-derived stem cells was effective to increase the viability of the random skin flaps in rats.